Analysis of the Russian Market for Artificial Lung Ventilation Units - Yu. A. Zuenkova (Управленческие науки)
The medical industry is strategically important for the national economy and healthcare. The COVID-19 pandemic has shown the importance of local MedTech capacity and production facilities to meet the needs of the healthcare market. The purpose of the study is to conduct the analysis of the Russian market of artificial lung ventilation devices (ventilators). Materials and methods. The analysis of customs statistics data was carried out by the Ministry of Foreign Economic Activity of the Russian Federation (RF), the Federal Customs Service of Russia (FCS Russia), Federal Tax Service of Russia (FTS Russia), Federal State Statistics Service (Rosstat), the Ministry of Economic Development of the Russian Federation, the Ministry of Health of the Russian Federation, Federal Service for Supervision in the Sphere of Health Care (Roszdravnadzor) as well as the Commodity Nomenclature of Foreign Economic Activity (FEACN RF). During the study, statistical methods were used, as well as analysis and synthesis. The author determined the number of ventilator models present on the Russian market, the dynamics of their import and export volumes (during and after the COVID-19 pandemic) in the country context. Results. Up to 200 ventilator models from 87 vendors are represented on the RF market. The volume of imports of ventilators in 2022 amounted to $ 32.0 million (2.2 billion rubles). After a jump in imports during the COVID-19 pandemic in 2021, the volume of deliveries fell to 43 million (-23% by 2019), and in 2022 the decline was 25% (-44% by 2019). In 2020, the imports volume of value of ventilators increased 6.5 times. In 2021, the volume of imports and exports immediately fell below the indicators of the pre-crisis period. Deliveries from Germany decreased by 52%, the USA — by 86%, Korea — by 98%, France — by 29%, Slovakia — by 36%, and from Sweden stopped altogether. China has increased the volume of imports, adding 81% by 2021, and Switzerland to 41%. The volume of exports amounted to $ 383 thousand (410 million rubles), including exports to the EAEU countries amounted to $ 88 thousand, exports to non-CIS countries decreased by 95% (from $ 6.7 million to $ 0.3 million in 2021-2022). Conclusion. The results of this study can be applied by Russian ventilator manufacturers to assess the growth potential, as well as by government authorities to set priorities for strategic development by segments of the medical devices market.